La hora de la TV: la incursión de la televisión y telenovela en la vida cotidiana de la ciudad de México (1958-1966) - Ramírez Bonilla, Laura Camila (El Colegio de México, A.C., 2015)
Television and television genres have a life of their own. In the Mexican case, telenovelas can be seen as the first genre authentically conceived and created for television. Since their appearance in Mexico in June 1958 on Telesistema-Canal 4, they not only recapitulated the stereotypes, myths and moral concerns of society at that time, but also became part of the daily life of their spectators, still expectant neophytes. The first melodramas were an urban phenomenon and characterized the growth of the middle class. The genre’s audience was created by its appearance and viewers actively integrated what they saw on screen into their family life. Watching telenovelas was a primordially domestic act while simultaneously being a collective one, shared among many people. Understanding this genre as a product made to provide meaning and using an analysis that demands both the study of narrative content as well an analysis of the medium itself and its spectators, this article identifies the way in which the arrival of television (and telenovelas in particular) made an impact on the daily life of television viewers in Mexico City. Did the arrival of television melodramas, between 1958 and 1966, introduce a new sense of the everyday in the viewing public? How did this new sense of everyday life express itself in space, time, routines, tastes and the collective imagination of viewers? This article is supported by the audiovisual content of the first television melodramas transmitted in Mexico, their reception in television magazines and the press in general, their accompanying advertising and the experiences of middle class individuals and families who were interviewed and surveyed on the subject.